Argon plasma coagulation for the treatment of chronic radiation proctitis – real-world data from Indonesian National Cancer Center - Lianda Siregar; Imelda Maria Loho; Agus Sudiro Waspodo; Rahmanandhika Swadari; Benedicta Audrey Maharani (The Indonesian Society for Digestive Endoscopy, 2021)
Background: This study aimed to evaluate the endoscopic features and clinical outcome of patients with chronic radiation proctitis (CRP) at one year after argon plasma coagulation (APC) treatment. Method: Between March 2016 and September 2019, a total of 48 female patients with CRP were treated with APC and their medical records were retrospectively reviewed. APC treatment was done every 3 to 54 weeks, with a median of 8 weeks. Number of APC was decided by the treating physician according to the severity of illness. Endoscopic and clinical features at one year after the final APC were recorded as the effectiveness of APC.Results: Of 48 patients, 26 patients were included in this study. Number of APC sessions varied between 1 to 5 sessions of APC for each patient. Of 26 patients, 22 patients achieved clinical improvement and four patients did not achieve clinical improvement at one year after the last APC session. Of the four patients who failed to achieve clinical improvement, two patients underwent surgery, one patient had occasional mild rectal bleeding, and one patient required regular transfusion. Of 22 patients with clinical improvement at one-year after the last APC, improvement of endoscopic features was found in 20 patients. Of four patients who did not achieve endoscopic improvement, diagnostic colonoscopy showed telangiectasis of more than 50% of rectal surface in 1 patient, presence of blood in 2 patients, and presence of ulceration of 1 cm in 1 patient.Conclusion: APC is an effective treatment option for CRP.